Unraveling the neurophysiological underpinnings of social anxiety through body language: An ERP study - Jiajia Jin; Xinyi Zhu; Wen Lian; Lu Fan (Comprehensive Psychiatry, 2025)
Objective: Body language plays a vital role in emotion perception, yet the involuntary neural mechanisms through which individuals with social anxiety process these signals remain unclear. This research investigates these mechanisms by analyzing visual components such as P3a, P1, and N190 within a three-stimulus oddball paradigm. Method: Participants were classified into high social anxiety (HSA, n = 31) and low social anxiety (LSA, n = 26) groups using the Liebowitz Social Anxiety Scale (LSAS). The paradigm employed custom-designed distractors depicting positive, negative, and neutral body expressions to examine the involuntary processing of these stimuli. Results: The findings indicate that individuals with high social anxiety (HSA) showed significantly higher P3a amplitudes than those with low social anxiety (LSA), especially for positive body expressions. In contrast, negative expressions elicited the weakest amplitudes. The N190 component responded most strongly to positive expressions and least to negative ones, while the P1 component showed uniform responses across all types. Conclusions: HSA individuals process body expressions more intensely and are highly sensitive to them, regardless of valence. This insight can inform interventions targeting their cognitive and emotional biases.